Pengaruh Stres Kerja Terhadap Kepuasan Kerja Perawat Di Ruang Rawat Inap Rumah Sakit Krakatau Medika Cilegon - Widiharti, Lisa (POLITEKNIK NEGERI BANDUNG, 2016)
Job satisfaction can improve durability individuals to stress and impacts of stress and on the other hand, stress that perceived by an individual can be a source of discontent. This research aims to know the influence of work stress of job satisfaction of nurses in internist room of Krakatau Medika Hospital Cilegon. Research method the used is the descriptive method to 215 nurses who have experienced nurses' room of Krakatau Medika Hospital Cilegon. While to test the research hypothesis, the authorize a simple regresion analysis method with the help of software SPSS 20. The results showed job stress in nurses in the inpatient unit Krakatau Medika Hospital in the moderate category is 2.88 and the job satisfaction of nurses are in a high category. Work stress experienced by nurses at Krakatau Medika Hospital has a positive effect on job satisfaction, so the impact of positive stress is used as a motivational well as improved performance. The results of correlation calculations, the independent variables on satisfaction positive relationships with low classification, the amount of work stress on job satisfaction, which is 12.4% and the remaining 87.6% influenced by other factors not described in this study, other factors such as remuneration, staffing, work environment, leadership style, and so on.